2020
DOI: 10.3390/microorganisms8050711
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Optimization of the Physico-Chemical Parameters for Pigment Production in Submerged Fermentation of Talaromyces albobiverticillius 30548

Abstract: Talaromyces albobiverticillius 30548 is a marine-derived pigment producing filamentous fungus, isolated from the La Réunion island, in the Indian Ocean. The objective of this study was to examine and optimize the submerged fermentation (SmF) process parameters such as initial pH (4–9), temperature (21–27 °C), agitation speed (100–200 rpm), and fermentation time (0–336 h), for maximum production of pigments (orange and red) and biomass, using the Box–Behnken Experimental Design and Response Surface Modeling (BB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…The closer the R2 value to 1.00, the stronger the model is, and the better it predicted the observed response. It was suggested that the R2 value should be at least 0.80, for a good model tness (Venkatachalam et al 2020). Here, the calculated R2 value of 0.9543 (Supplementary Table 2), indicated that 4.57% of the total variation could not be explained by the empirical model; this expresses a good enough quadratic t to navigate the design space.…”
Section: Resultsmentioning
confidence: 81%
“…The closer the R2 value to 1.00, the stronger the model is, and the better it predicted the observed response. It was suggested that the R2 value should be at least 0.80, for a good model tness (Venkatachalam et al 2020). Here, the calculated R2 value of 0.9543 (Supplementary Table 2), indicated that 4.57% of the total variation could not be explained by the empirical model; this expresses a good enough quadratic t to navigate the design space.…”
Section: Resultsmentioning
confidence: 81%
“…In previous studies, the major influencing factors (pH, temperature, agitation speed, and fermentation time) for fungal growth and pigment production from T. albobiverticillius 30548 were screened and optimized by culturing the strain in potato dextrose broth alone (PDB, BD Difco, Franklin Lakes, NJ, USA) [ 68 ]. Then, to determine the most appropriate nutrient sources for maximum pigments production, different carbon and nitrogen sources were chosen for an OVAT study (one-variable-at-a-time analysis).…”
Section: Methodsmentioning
confidence: 99%
“…108 In with optimisation by response surface methodology (RSM), statistically valid models for metabolite production can be obtained. 109 Alternatively, if the DNA sequence data is available, genomic data mining can be performed. Comparison to annotated sequence data with known functions can not only confirm the existence of hidden biosynthetic gene clusters in the target organism's DNA but also identify them.…”
Section: Challenges For Application Of Biogenic Dyesmentioning
confidence: 99%